2022
DOI: 10.5455/javar.2022.i583
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Aspergilli from commercial chicken in selected areas of Bangladesh

Abstract: Objectives: This study was designed to isolate, identify, and determine the prevalence of Aspergilli in commercial chicken in selected areas of Bangladesh. Materials and Methods: A total of 50 lung samples from suspected dead chickens, comprising broilers (n = 32) and layers (n = 18), aged between 5 days and 45 weeks, were collected from poultry farms located in the Gazipur district in Bangladesh. Fungi were primarily identified based on the colony morphology using potato dextrose agar (PDA). DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
3
4
0
Order By: Relevance
“…Aspergillus infections have been documented in all ages of birds, but the extremes of age are the most affected [ 37 ]. In the present study, a higher risk was obtained in birds older than 16 days, such as in the research in Bangladesh [ 25 ], in which a higher infection of Aspergillus flavus was reported in animals older than 3 weeks. In addition, also in Bangladesh, a higher mortality was observed and associated with aspergillosis in chickens of Isa Brown and Hy-Line breeds from three to eight weeks of age [ 34 ].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Aspergillus infections have been documented in all ages of birds, but the extremes of age are the most affected [ 37 ]. In the present study, a higher risk was obtained in birds older than 16 days, such as in the research in Bangladesh [ 25 ], in which a higher infection of Aspergillus flavus was reported in animals older than 3 weeks. In addition, also in Bangladesh, a higher mortality was observed and associated with aspergillosis in chickens of Isa Brown and Hy-Line breeds from three to eight weeks of age [ 34 ].…”
Section: Discussionsupporting
confidence: 62%
“…In another investigation carried out in Egypt, Aspergillus flavus was the most common, at 60% (24/40) [ 28 ]. Mixed isolates have also been obtained in other investigations in low proportions [ 25 , 28 , 30 ]. Regarding the occurrence of Aspergillus terreus, Aspergillus candidus , and Aspergillus ochraceus (belonging to Aspergillus section Circumdati ), it has also been reported with less frequency [ 23 , 31 ].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations